A Fashi Lymphoproliferative Phenotype Reveals Non-Apoptotic Fas Signaling in HTLV-1-Associated Neuroinflammation - Menezes, Soraya Maria; Leal, Fabio E.; Dierckx, Tim; Khouri, Ricardo; Decanine, Daniele; Silva-Santos, Gilvaneia; Schnitman, Saul V.; Kruschewsky, Ramon; López, Giovanni; Alvarez, Carolina; Talledo, Michael; Gotuzzo, Eduardo; et al. (Frontiers in Immunology, 2017)
Human T-cell lymphotropic virus (HTLV)-1 was the first human retrovirus to be associated to cancer, namely Adult T-cell Leukemia (ATL), but its pathogenesis remains enigmatic, since only a minority of infected individuals develops either ATL or the neuroinflammatory disorder HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). A functional FAS -670 polymorphism in an interferon (IFN)-regulated STAT1-binding site has been associated to both ATL and HAM/TSP susceptibility. Fashi T stem cell memory (Tscm) cells have been identified as the hierarchical apex of ATL, but have not been investigated in HAM/TSP. In addition, both FAS and STAT1 have been identified in an IFN-inducible HAM/TSP gene signature, but its pathobiological significance remains unclear. We comprehensively explored Fas expression (protein/mRNA) and function in lymphocyte activation, apoptosis, proliferation and transcriptome, in PBMC from a total of 47 HAM/TSP patients, 40 asymptomatic HTLV-1-infected individuals (AC) and 58 HTLV-1 -uninfected healthy controls. Fas surface expression followed a two-step increase from HC to AC and from AC to HAM/TSP. In HAM/TSP, Fas levels correlated positively to lymphocyte activation markers, but negatively to age of onset, linking Fashi cells to earlier, more aggressive disease. Surprisingly, increased lymphocyte Fas expression in HAM/TSP was linked to decreased apoptosis and increased lymphoproliferation upon in vitro culture, but not to proviral load. This Fashi phenotype is HAM/TSP-specific, since both ex vivo and in vitro Fas expression was increased as compared to multiple sclerosis another neuroinflammatory disorder. To elucidate the molecular mechanism underlying non-apoptotic Fas signalling in HAM/TSP, we combined transcriptome analysis with functional assays, i.e. blocking vs. triggering Fas receptor in vitro with antagonist and agonist- anti-Fas mAb, respectively. Treatment with agonist anti-Fas mAb restored apoptosis, indicating biased but not defective Fas signalling in HAM/TSP. In silico analysis revealed biased Fas signalling towards proliferation and inflammation, driven by RelA/NF-kB. Correlation of Fas transcript levels with proliferation (but not apoptosis) was confirmed in HAM/TSP ex vivo transcriptomes. In conclusion, we demonstrated a two-step increase in Fas expression, revealing a unique Fashi lymphocyte phenotype in HAM/TSP, distinguishable from multiple sclerosis. Non-apoptotic Fas signalling might fuel HAM/TSP pathogenesis, through increased lymphoproliferation, inflammation and early age of onset.